PERAN TEKNOLOGI INFORMASI DALAM MENGEMBANGKAN PEMAHAMAN SISWA TENTANG AJARAN ISLAM DI MTSN 3 LABUHAN BATU - Putri Mega (Yayasan Baitul Hikmah al-Zain, 2025)
The role of information technology in education is growing rapidly, including in the teaching of the Islamic religion. This research aims to examine how information technology can be used to develop students' understanding of Islamic teachings at MTsN 3 Labuhan Batu. Information technology allows the use of various learning media that are more interesting, interactive and easily accessible to students. In this research, the method used is qualitative with a descriptive approach. Data was collected through interviews, observation and documentation at MTsN 3 Labuhan Batu. The research results show that information technology, such as the use of computer devices, the internet, and multimedia-based learning applications, plays an important role in increasing students' understanding of Islamic teaching material. The use of learning videos, e-books and online platforms allows students to more easily understand Islamic concepts in depth and relevant to current developments. Apart from that, the use of social media also provides opportunities for students to discuss and share information related to Islamic teachings. Thus, the use of information technology at MTsN 3 Labuhan Batu contributes positively to enriching the teaching and learning process and increasing understanding of Islamic teachings among students.